Transcriptomic Remodelling of Fetal Endothelial Cells During Establishment of Inflammatory Memory - Weiss, Elisa; Vlahos, Amanda; Kim, Bowon; Wijegunasekara, Sachintha; Shanmuganathan, Dhanya; Aitken, Thomas; Joo, Ji-Hoon E.; Imran, Samira; Shepherd, Rebecca; Craig, Jeffrey M.; Green, Mark; Hiden, Ursula; et al. (Frontiers in Immunology, 2021)
Inflammatory memory involves the molecular and cellular ‘reprogramming’ of innate immune cells following exogenous stimuli, leading to non-specific protection against subsequent pathogen exposure. This phenomenon has now also been described in non-hematopoietic cells, such as human fetal and adult endothelial cells. In this study we mapped the cell-specific DNA methylation profile and the transcriptomic remodelling during the establishment of inflammatory memory in two distinct fetal endothelial cell types – a progenitor cell (ECFC) and a differentiated cell (HUVEC) population. We show that both cell types have a core transcriptional response to an initial exposure to a viral-like ligand, Poly(I:C), characterised by interferon responsive genes. There was also an ECFC specific response, marked by the transcription factor ELF1, suggesting a non-canonical viral response pathway in progenitor endothelial cells. Next, we show that both ECFCs and HUVECs establish memory in response to an initial viral exposure, resulting in an altered subsequent response to lipopolysaccharide. While the capacity to train or tolerise the induction of specific sets of genes was similar between the two cell types, the progenitor ECFCs show a higher capacity to establish memory. Among tolerised cellular pathways are those involved in endothelial barrier establishment and leukocyte migration, both important for regulating systemic immune-endothelial cell interactions. These findings suggest that the capacity for inflammatory memory may be a common trait across different endothelial cell types but also indicate that the specific downstream targets may vary by developmental stage.